Dysosmia and dysgeusia associated with duloxetine - Yoshida, Katsuyuki (BMJ Case Rep, 2017)
Common adverse effects of serotonin–norepinephrine reuptake inhibitors are nausea, dry mouth, dizziness and headache. We describe the case of a patient with dysosmia and subsequent dysgeusia associated with duloxetine. A 68-year-old Japanese woman with a history of type 1 diabetes mellitus, hypertension, insomnia and reflux esophagitis presented to a local hospital with bilateral leg pain; she was treated with duloxetine. However, after 4 weeks, she sensed rotten egg smell, experienced nausea and vomiting and was admitted to our hospital. We diagnosed dysosmia using the T&T olfactometer threshold test and dysgeusia using filter paper disk method. Taste was assessed using electrogustometry. We suspected that dysosmia and dysgeusia were adverse effects of duloxetine. After stopping duloxetine, her symptoms gradually subsided and the above test results improved, despite continuing the other ongoing medication. To the best of our knowledge, this is the first case report of dysosmia and dysgeusia associated with duloxetine.